Endoscopic Pancreato-Biliary Interventions - Raza, Ali; Krishnan, Kumar (Digestive Disease Interventions, 2018)
Endoscopic ultrasound (EUS) and endoscopic retrograde cholangiopancreatography (ERCP) play a critical role in the diagnosis and management of benign and malignant pancreatobiliary diseases. In the last several years, role of ERCP has evolved from just a diagnostic procedure to mostly a therapeutic procedure. It plays a key role in the diagnosis of indeterminate biliary strictures and evaluation of bile leaks. Therapeutic ERCP utilizes various techniques for the extraction of biliary and pancreatic stones, management of bile leaks, and the treatment of malignant and benign strictures. EUS plays a central role in tissue acquisition for diagnostic purposes. Therapeutic applications of EUS have significantly increased in the recent years and include management of pancreatic fluid collections, pancreatic necrosis, drainage of the biliary obstruction, gall bladder drainage, and EUS-assisted ERCP. These procedures have good efficacy and acceptable side effect profile when performed by expert endoscopists at tertiary care medical centers.
Keywords: endoscopic retrograde cholangiopancreatography; endoscopic ultrasound; biliary interventions; pancreatic disease